(untitled) (Research, Society and Development, 2021)
The present work aims to discuss the communication of palliative care nurses with patients with breast cancer. In this way, it is essential to have a brief explanation about the pathology, its incidence in women, in the world and in Brazil, so that the nurse has technical and empirical knowledge about the disease. Methods: This is a literature review, with a selection of articles published between the years 2013 to 2021 in the database BVS, LILACS, SCIELO, BDENF and Academic Google. Results: At first, about 2371 publications were found, which after a thorough filtering and framing the eligibility criteria, resulted in 09 articles, analyzed through a table in Word. Conclusion: Through the research carried out for the making of this, the importance of humanized communication between the nursing team and the patient in palliative care was clear, since the health professional, due to his technical-theoretical knowledge, acts as a support base for the patient, who needs to understand about the pathology that affects him, its symptoms, severity and consequences, in an holistically and professionally way.